Persepsi Generasi Muda Terhadap Pekerjaan Sebagai Petani di Desa Picuan Kecamatan Motoling Timur Kabupaten Minahasa Selatan - Kawulur, Kartika Chelsea; Benu, Noortje Marsellanie; Tambas, Jane Sulinda (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to describe the perception of the younger generation towards farming in Picuan Village, East Motoling Sub-district, South Minahasa Regency. This research was conducted from May 2024 to July 2024. The sampling method in this study used purposive sampling. The data collection method in this study used the sample survey method. The type of data used in the research is primary data obtained through direct interviews with youth using a list of statements (questionnaire). Secondary data was obtained from related institutions, namely Picuan Village Office, research results and literature related to the research conducted. The overall research results obtained an overall index of 83.37% with the criteria of agreement. The young generation in Picuan Village agrees that farming provides high income. Through education, young people can increase productivity in farming. Working as a farmer is inseparable from the risk of failure. Young people in Picuan village agree that risks such as price fluctuations, weather changes, and crop pests and diseases affect their work as farmers. Younger generations agree that farming is hard and tiring but it does not damage their physical appearance and working hours as a farmer can be self-regulated by farmers.